PELAYANAN PUBLIK PERANGKAT DESA TERHADAP KEPUASAN MASYARAKAT DALAM PEMBUATAN KK (STUDI DESKRIPTIF DESA JEROWARU, KECAMATAN JEROWARU, KABUPATEN LOMBOK TIMUR) - Jakaria Jakaria; Rispawati Rispawati; Mursini Jahiban (Jurnal Pendidikan Sosial Keberagaman, 2020)
ABSTRACKThis study aims to determine the public service standards of village apparatus on community satisfaction and the factors that influence public service standards based on Public Service Standards according to Ministerial Decree PAN number 63 / KEP / M.PAN / 7/2003 in Jerowaru Village, Jerowaru District, Regency East Lombok. The subject of this research is the Head of Service and Service Staff, the subject of this study was chosen because most know the administration of government services in the village of Jerowaru, Jerowaru District, East Lombok Regency. The informants in this research are the people (who are doing a letter of introduction to the Family Card / KK). Date collection techniques used are, interview, observation, and documentation. The results showed that 1) The application of public service standards was in accordance with Minister of PAN Decree number 63 / KEP / M.PAN / 7/2003 such as service procedures, service requirements, clarity of service officers, discipline of service officers Responsibility of service officers, ability of service officers , Speed of service, Justice in getting services, Courtesy and friendliness of officers, Certainty of service schedules, Comfort of the environment and Safety of services, in Jerowaru Village, jerowaru sub-district, East Lombok Regency, this can be seen in the service activities carried out by village service employees, 2) The driving factors and obstacles that affect public services in Jerowaru village. The driving factors are cooperation between service Internal and Eksternal, supporting facilities and evaluation meetings related to services performed. Then the inhibiting factors are the lack of employees in the field of service, inadequate facilities and lack of understanding from the novice community that makes the Family card.ABSTRAK Penelitian ini bertujuan untuk mengetahui standar pelayanan public perangkat desa terhadap kepuasan masyarakat dan Faktor-faktor yang mempengaruhi standar pelayanan publik berdasarkan Standar Pelayanan Publik menurut Keputusan Menteri PAN nomor 63/KEP/M.PAN/7/2003 di Desa Jerowaru, Kecamatan jerowaru, Kabupaten Lombok Timur. Subyek Penelitian ini adalah Kepala Bidang Pelayanan dan Pegawai Pelayanan, subyek penelitian ini dipilih dikarenakan paling mengetahui penyelenggaraan Pelayanan pemerintahan di Desa Jerowaru, Kecamatan Jerowaru, Kabupaten Lombok Timur. Informan dalam penelitian adalah masyarakat (yang sedang melakukan pembuatan surat penghantar Kartu Keluarg/KK). Teknik pengumpulan data yang digunakan yakni, wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan, bahwa 1) Penerapan standar pelayanan publik sudah sesuai dengan Keputusan Menteri PAN nomor 63/KEP/M.PAN/7/2003 seperti Prosedur pelayanan, Persyaratan pelayanan, Kejelasan petugas pelayanan, Kedisiplinan petugas pelayananTanggung jawab petugas pelayanan, Kemampuan petugas pelayanan, Kecepatan pelayanan, Keadilan mendapatkan pelayanan, Kesopanan dan keramahan petugas, Kepastian jadwal pelayanan, Kenyamanan lingkungan dan Keamanan pelayanan, di Desa Jerowaru, Kecamatan jerowaru, Kabupaten Lombok Timur, hal ini terlihat dalam kegiatan pelayanan yang dilakukan pegawai pelayanan desa,2) Faktor Internal dan eksternal yang mempengaruhi pelayanan publik di desa jerowaru. Faktor Internal yaitu adanya pola pelayanan umum organisas, penyedian fasilitas penunjang, sumber daya manusia. Kemudian faktor Eksternal yaitu pola layanan distribusi Jasa dan pola layanan dan tata cara pembuatan Kartu Keluarga